2006
DOI: 10.1021/om060673b
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogenation of Aldehydes, Esters, Imines, and Ketones Catalyzed by a Ruthenium Complex of a Chiral Tridentate Ligand

Abstract: A noVel ruthenium complex prepared from a chiral tridentate amine functionalized phosphine has been characterized by X-ray crystallography and been found to be actiVe in the hydrogenation of an unprecedented range of CdO and CdN double bonds, including the enantioselectiVe hydrogenation and transfer hydrogenation of normally unreactiVe bulky ketones with up to 90% ee.Reduction of CdO and CdN double bonds using molecular hydrogen is, due to its low cost and complete atom efficiency, a very important process in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(55 citation statements)
references
References 38 publications
2
50
0
Order By: Relevance
“…These catalysts give excellent results in the hydrogenation of a range of acetophenone derivatives, as have a number of structurally related catalysts [4,5]. However, [RuCl 2 (BINAP)(DAIPEN)] and related catalysts do have some important limitations, that have spurred significant interest in new catalyst development [6-21]. Given that so many drugs, agrochemicals, materials, and natural products can be disconnected back to enantiopure secondary alcohols, it is of significant importance to extend asymmetric hydrogenation chemistry such that it is effective for every major class of substrate.…”
Section: Resultsmentioning
confidence: 99%
“…These catalysts give excellent results in the hydrogenation of a range of acetophenone derivatives, as have a number of structurally related catalysts [4,5]. However, [RuCl 2 (BINAP)(DAIPEN)] and related catalysts do have some important limitations, that have spurred significant interest in new catalyst development [6-21]. Given that so many drugs, agrochemicals, materials, and natural products can be disconnected back to enantiopure secondary alcohols, it is of significant importance to extend asymmetric hydrogenation chemistry such that it is effective for every major class of substrate.…”
Section: Resultsmentioning
confidence: 99%
“…Reduction of other carboxylic acid derivatives, some of which are even less activated to reduction, are also of interest. 27 I believe this general class of catalyst (chiral ligands with PNX-donor sets) could well have other applications in enantioselective catalysis outside the hydrogenation arena; enantioselective C-C bond forming reactions are also conceivable with these systems. Overall, in the last ten years, a wide range of catalytic chemistry has been made possible by using the more general class of bifunctional tridentate ligands.…”
Section: Discussionmentioning
confidence: 99%
“…While these can be removed by chromatography or recrystallisation, a good procedure was to use microwave heating to heat the ligand and [RuCl 2 (dmso) 4 ] in THF at 120°C for 20 minutes to give the desired air-stable complex in pure form such that it can be dried and used immediately. 27 The structure of 2 was determined by X-ray crystallography. We have also found that the phosphine-diamine ligand or its borane complex can simply be added with [RuCl 2 (dmso) 4 ] to hydrogenation reactions to generate the catalysts in situ; a method we have used in some cases where novel ligands were only prepared on a very small scale.…”
Section: Hydrogenation Of Low-reactivity Carbonyl Functionsmentioning
confidence: 99%
“…Some of them display high reactivity and selectivity in many catalytic transformations and, in particular, in the hydrogenation of different unsaturated compounds, such as α,β-unsaturated ketones and imines, using molecular H 2 and transfer hydrogenation (TH) protocols as reducing agents [6][7][8][9]. The employment of these last methodologies offers attractive advantages including the use of inexpensive and easy to handle hydrogen donors instead of explosive hydrogen gas, mild reaction conditions, and the possibility of using environmentally friendly solvents such as water [10][11][12].…”
Section: Introductionmentioning
confidence: 99%